2012
DOI: 10.1111/gfs.12016
|View full text |Cite
|
Sign up to set email alerts
|

Animal saliva has stronger effects on plant growth than salivary components

Abstract: Mutualism between plants and animals demonstrates that grazing has positive impacts on plant growth. Animal saliva plays an important role in plant–herbivore interactions, and various salivary components work for the beneficial relationship. This study was performed to compare responses of Leymus chinensis (Trin.) Tzvelev. (Poaceae) to sheep saliva and two salivary components. One randomized block designed experiment was conducted in 2007 with six treatments: control, clipping with water, with saliva, with epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…All such effects impact the acquisition and allocation of plant resources including water, nutrients and photo assimilates and as such, observations regarding changes in growth rates are not uncommon. Nevertheless, evidence has suggested that application of saliva to the leaf surface elicits growth promotion in addition to these effects (Table 1) (Reardon et al 1972(Reardon et al , 1974Dyer and Bokhari 1976;Reardon and Merrill 1978;Dyer 1980;Howe et al 1982;Kato et al 1993;Rooke 2003;Loeser et al 2004;Teng et al 2010;Gullap et al 2011;Liu et al 2012;Li et al 2014). Deposition of saliva onto grasses during grazing occurs as animals lick forage to direct biomass into their mouths, or the mouth come into contact with grass; both of which leads to the transfer of chemicals to the un-grazed plant tissue (McNaughton 1985;Liu et al 2012;Huang et al 2014).…”
Section: Pasture Production Terminology and The Challenges Of Inter-s...mentioning
confidence: 99%
See 3 more Smart Citations
“…All such effects impact the acquisition and allocation of plant resources including water, nutrients and photo assimilates and as such, observations regarding changes in growth rates are not uncommon. Nevertheless, evidence has suggested that application of saliva to the leaf surface elicits growth promotion in addition to these effects (Table 1) (Reardon et al 1972(Reardon et al , 1974Dyer and Bokhari 1976;Reardon and Merrill 1978;Dyer 1980;Howe et al 1982;Kato et al 1993;Rooke 2003;Loeser et al 2004;Teng et al 2010;Gullap et al 2011;Liu et al 2012;Li et al 2014). Deposition of saliva onto grasses during grazing occurs as animals lick forage to direct biomass into their mouths, or the mouth come into contact with grass; both of which leads to the transfer of chemicals to the un-grazed plant tissue (McNaughton 1985;Liu et al 2012;Huang et al 2014).…”
Section: Pasture Production Terminology and The Challenges Of Inter-s...mentioning
confidence: 99%
“…Previous studies have also attempted to use 'synthetic' saliva as a substitute, and was a concept initially proposed by Jameson (1964). However, results of studies that used a synthetic version have often suggested that the growth response of plants do not elicit the same response compared to the use of real saliva (Reardon et al 1974;McNaughton 1985;Lamy et al 2010;Huang et al 2014;Li et al 2014). Animal saliva used in contrast, has been found to have a larger impact on plant growth than any synthetic substrate used, further contributing to the complexity of understanding the impact that individual substrates may have (McNaughton 1985;Li et al 2014).…”
Section: Species Specific Interactions and Sampling Protocols Limit E...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the important role of JA, the saliva of herbivores is also very important in the process of animal feeding. For example, Li et al compared the effects of water, sheep saliva, epidermal growth factor (EGF), thiamine, and the mixture of EGF and thiamine on the growth of clipped L. chinensis and found that the biomass and buds increased after sheep saliva treatment rather than water treatment, although the animal saliva components had no cumulative effect on plant growth [ 17 ]. Moreover, animal saliva can also affect the level of hormones in plants [ 18 ].…”
Section: Introductionmentioning
confidence: 99%